2020
DOI: 10.1128/jvi.01930-19
|View full text |Cite|
|
Sign up to set email alerts
|

A Single Amino Acid at Position 431 of the PB2 Protein Determines the Virulence of H1N1 Swine Influenza Viruses in Mice

Abstract: The frequent reassortment among different influenza viruses in pigs adds complexity to the epidemiology of swine influenza. The diverse viral virulence phenotypes underline the need to investigate the possible genetic determinants for evaluating the pandemic potential to human public health. Here, we found that multiple genotypes of influenza viruses cocirculate in the swine population in Liaoning Province, China. Furthermore, we pinpointed a single amino acid at position 431 in the PB2 protein which plays a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…The amino acids at positions 251, 271, 588, 431, 590, and 591 of the PB2 protein suggested that these viruses could adapt to mammalian hosts [ 13 , 31 , 32 , 33 ], but 627E and 701N indicated the relatively low pathogenicity of these viruses [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The amino acids at positions 251, 271, 588, 431, 590, and 591 of the PB2 protein suggested that these viruses could adapt to mammalian hosts [ 13 , 31 , 32 , 33 ], but 627E and 701N indicated the relatively low pathogenicity of these viruses [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The EA H1N1 SIV was first detected in Liaoning in 2006 and became prevalent gradually. Since 2014, reassortant EA H1N1 or H1N2 SIVs have been detected in Liaoning [ 13 ]. From 2014 to 2016, three different recombinated EA H1N1 SIVs have been identified, including two triple reassortants and one double reassortant, as shown in Figure 5 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Avian-like H1N1 SIV was first isolated from pigs in 1979 in Belgium ( 5 ) and has since spread to many European and Asian countries ( 6 8 ); for this reason, it is referred to as Eurasian avian-like H1N1 SIV (EA H1N1 SIV). After the reintroduction of the human pandemic 2009/H1N1 virus to pigs, multiple genotypes of reassortant H1N1 and H1N2 SIVs bearing the hemagglutinin (HA) gene of EA H1N1 SIV have replaced the pure EA H1N1 SIV and are currently prevalent in swine populations in China ( 9 13 ). Sporadic infections caused by EA H1N1 or EA H1N1-like viruses and antigenic variation within these viruses pose new potential threats to public health and also present new challenges to the pig industry ( 10 , 12 , 14 19 ).…”
Section: Introductionmentioning
confidence: 99%